Maternal and Infant Iron Status Are Related to Mother-Infant Interactions (P10-094-19) - Ciulei, Mihaela (Curr Dev Nutr, 2019)
OBJECTIVES: To examine the association between iron status and mother-infant interactions in dyads from rural Bangladesh. METHODS: Maternal-infant interactions were assessed in dyads from a substudy nested within a randomized controlled trial in rural Bangladesh. Recorded interactions (10 minutes free-play; 2 minutes diapering) at baseline (BL) (infant age 6–18 mo; n = 116), midline (ML) (+ 3 mo; n = 324), and endline (EL) (+ 6 mo; n = 336) were coded per the Emotional Availability Scales (EAS; 4 maternal scales: sensitivity, structuring, non-intrusiveness, non-hostility; 2 child scales: responsiveness, involvement). Ferritin (Ft), transferrin receptor (TfR), and hemoglobin (Hb; in infants only) concentrations were measured at BL and EL. Group differences (categorized by iron status irrespective of intervention group) were assessed via ANCOVA (covariates: socioeconomic status, mean upper arm circumference, weight-for-age Z-score, child sex and age and maternal depressive symptoms (Center for Epidemiologic Studies Depression Scale) and reasoning abilities (Raven's Progressive Matrices)). Stepwise regressions were run to determine predictors of the EAS scores. RESULTS: Prevalence of iron deficiency (ID; Ft < 23.7 mg/L) in infants dropped from 55% to 38% and of ID anemia (IDA; Hb < 110 g/L) from 53% to 32%, respectively. Only 12% of mothers were ID (Ft < 15.0 µg/L). Dyads of iron sufficient (IS) infants had higher involvement scores at BL and ML (both P ≤ 0.04), and higher sensitivity and structuring but lower non-intrusiveness scores (all P < 0.01) at ML vs dyads of ID infants. In the regressions, iron status of the mother and/or child was significantly predictive of maternal behaviors for most of the EA scales at all time points with better iron status predicting better behavioral scores except for non-intrusiveness. At BL (but not EL), child BL TfR was negatively related to involvement and responsiveness. No other iron status variables were associated with child behavior at any time point. CONCLUSIONS: An association exists between maternal and infant iron status and dyadic interaction. Adequate iron status appears to benefit the dyadic relationship. FUNDING SOURCES: USAID through the Johns Hopkins Global Research Activity Cooperative Agreement.